Mechanical strength of a new plate compared to six previously tested opening wedge high tibial osteotomy implants - Arnaud Diffo Kaze; Stefan Maas; James Belsey; Alexander Hoffmann; Romain Seil; Ronald van Heerwaarden; Dietrich Pape (Journal of Experimental Orthopaedics, 2019)
Abstract Background This study aimed to assess the mechanical static and fatigue strength provided by the FlexitSystem plate in medial opening wedge high tibial osteotomies (MOWHTO), and to compare it to six previously tested implants: the TomoFix small stature, the TomoFix standard, the ContourLock, the iBalance, the second generation PEEKPower and the size 2 Activmotion. Thus, this will provide surgeons with data that will help in the choice of the most appropriate implant for MOWHTO. Methods Six fourth-generation tibial bone composites underwent a MOWHTO and each was fixed using six FlexitSystem plates, according to standard techniques. The same testing procedure that has already been previously defined, used and published, was used to investigate the static and dynamic strength of the prepared bone-implant constructs. The test consisted of static loading and cyclical loading for fatigue testing. Results During static testing, the group constituted by the FlexitSystem showed a fracture load higher than the physiological loading of slow walking (3.7 kN > 2.4 kN). Although this fracture load was relatively small compared to the average values for the other Implants from our previous studies, except for the TomoFix small stature and the Contour Lock. During fatigue testing, FlexitSystem group showed the smallest stiffness and higher lifespan than the TomoFix and the PEEKPower groups. Conclusions The FlexitSystem plate showed sufficient strength for static loading, and average fatigue strength compared to the previously tested implants. Full body dynamic loading of the tibia after MOWHTO with the investigated implants should be avoided for at least 3 weeks. Implants with a wider T-shaped proximal end, positioned onto the antero-medial side of the tibia head, or inserted in the osteotomy opening in a closed-wedge construction, provided higher mechanical strength than implants with small a T-shaped proximal end, centred onto the medial side of the tibia head.